Anthracene-based MOFs crystalline material and preparation method and application thereof

By using anthracene-based MOFs crystalline material as fluorescent probes, the problem of expensive and inconvenient portability detection equipment in the prior art is solved, and efficient detection of trinitrophenol is achieved, which is selective and convenient.

CN116554494BActive Publication Date: 2025-04-18HARBIN INST OF TECH
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310574495.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-05-22
Publication Date
2025-04-18
Estimated Expiration
2043-05-22

AI Technical Summary

Technical Problem

The existing nitroaromatic explosive detection methods rely on large and expensive equipment, which are inconvenient to carry and costly, making it difficult to achieve convenient and effective detection.

Method used

The anthracene-based MOFs crystalline material was used as a fluorescent probe to prepare the material by solvent thermal synthesis method, and ground into powder and mixed with ethanol to form a suspension, which was used to detect the fluorescence signal changes in trinitrophenol (TNP).

Benefits of technology

The detection of trinitrophenol (TNP) at a concentration of 0 to 5 ppm is achieved, and is selective and not affected by other nitroaromatic explosives. It is suitable for the field of fluorescent sensors for environmental pollutants.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116554494B_ABST
    Figure CN116554494B_ABST
Patent Text Reader

Abstract

An anthracene-based MOFs crystalline material and its preparation method and application, which relates to a metal-organic framework material and its preparation method and application, and is intended to solve the technical problems of the existing nitroaromatic explosive detection method, the detection equipment being expensive and inconvenient to carry. The stoichiometric formula of the anthracene-based MOFs crystalline material of the present invention is {Cd·(4Cl‑BDC) 0.5 (STDC) 0.5 ·L} n , wherein 4Cl-BDC is deprotonated 2,3,5,6-tetrachloroterephthalic acid, STDC is deprotonated 4,4'-stilbene dicarboxylic acid, L is 9,10-bis(N-benzimidazolyl)anthracene, and n is a positive integer. The preparation method is to add soluble cadmium salt, 2,3,5,6-tetrachloroterephthalic acid, 4,4'-stilbene dicarboxylic acid and 9,10-bis(N-benzimidazolyl)anthracene to a solvent for solvothermal reaction. The material can be used to detect trace trinitrophenol of 0 to 5 ppm and is used in the field of fluorescent sensors for environmental pollutants.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of metal-organic framework materials, and in particular to a preparation method and application of an anthracene-based MOFs crystalline material. Background Art

[0002] Among the numerous organic pollutants, nitroaromatic explosives have become the most notable hazardous substances threatening human health and environmental safety due to their high toxicity and complex degradation process. Among them, trinitrophenol (TNP) is the most notable. As an important intermediate of industrial chemicals, it is widely used in the preparation of dyes and is also the main source of explosive raw materials. It is very easy to cause explosions in high temperature environments or when exposed to open flames or collisions, which harms the environment and has a negative impact on biodegradation. Once inhaled by humans or contacted through the skin, it will cause dermatitis, liver failure and other serious consequences, which is very detrimental to environmental safety and human health. Therefore, avoiding the threat of nitroaromatic explosives is an urgent issue that people are paying close attention to, and it is crucial to explore practical, convenient and effective methods for detecting nitroaromatic explosives.

[0003] At present, the detection technology for nitroaromatic explosives mostly relies on large-scale instruments and equipment, such as liquid chromatography, electrochemical sensing, Raman spectroscopy and cyclic voltammetry, etc. However, the disadvantages of large-scale instruments and equipment, such as inconvenience in carrying and high price, make it not an ideal method for detecting nitroaromatic explosives. Summary of the invention

[0004] The present invention provides an anthracene-based MOFs crystalline material and a preparation method and application thereof to solve the technical problems that the existing nitroaromatic explosive detection method and detection equipment are expensive and inconvenient to carry.

[0005] The stoichiometric formula of the anthracene-based MOFs crystalline material of the present invention is {Cd·(4Cl-BDC) 0.5 (STDC) 0.5 ·L} n , wherein 4Cl-BDC is deprotonated 2,3,5,6-tetrachloroterephthalic acid, STDC is deprotonated 4,4'-stilbene dicarboxylic acid, L is 9,10-bis(N-benzimidazolyl)anthracene, and n is a positive integer; the anthracene-based MOFs crystalline material crystallizes in the triclinic P-1 space group, and its structure is topological symbol {3 6 ·4 18 5 3 ·6} 8-connected 3D network; the unit cell parameters are: α=116.983(8)°,β=95.644(8)°,γ=102.146(9)°,the unit cell volume is

[0006] The preparation method of the above-mentioned anthracene-based MOFs crystalline material is carried out according to the following steps:

[0007] 1. Add soluble cadmium salt, 2,3,5,6-tetrachloroterephthalic acid, 4,4'-stilbene dicarboxylic acid and 9,10-bis(N-benzimidazolyl)anthracene to the solvent in sequence, dissolve all the materials and mix them evenly to obtain a mixed solution;

[0008] 2. Transfer the mixed solution to a reaction container, seal it and place it in a heating furnace, heat it from room temperature to 80-160°C at a heating rate of 3-10°C / min for a solvothermal reaction for 14-168 hours, and then lower the temperature of the heating furnace to room temperature within 12-24 hours by programmed cooling to obtain block crystals;

[0009] 3. Wash the block crystals with mother liquor and anhydrous ethanol in turn, collect the solids by centrifugation, and dry them to obtain an anthracene-based MOFs crystalline material. The anthracene-based MOFs crystalline material is a transparent yellow regular block crystal.

[0010] Preferably, the soluble cadmium salt described in step 1 is Cd(NO3)2·6H2O, CdCl2·H2O or (CH3COO)2Cd·2H2O.

[0011] Preferably, the organic ligand 9,10-bis(N-benzimidazolyl)anthracene described in step 1 has a molecular formula of C 28 H 18 N4.

[0012] Preferably, the solvent in step 1 is one or more of N,N-dimethylformamide (DMF), N,N-dimethylacetamide (DMA), N,N-diethylformamide (DEF), methanol, ethanol, acetonitrile and water.

[0013] Preferably, the molar ratio of the soluble cadmium salt to the organic ligand 2,3,5,6-tetrachloroterephthalic acid in step 1 is (2-5):1, the molar ratio of the soluble cadmium salt to the organic ligand 4,4'-stilbene dicarboxylic acid is (1-3):1, and the molar ratio of the soluble cadmium salt to the organic ligand 9,10-bis(N-benzimidazolyl)anthracene is (1-3):1.

[0014] Preferably, the dissolution in step 1 is carried out by mechanical stirring or ultrasonic oscillation, and the stirring or ultrasonic oscillation time is 10 to 60 minutes.

[0015] Preferably, the programmed cooling procedure in step 2 is: cooling at a cooling rate of 0.1°C / min to 0.5°C / min.

[0016] Preferably, the reaction container in step 2 is a polytetrafluoroethylene reactor or a high temperature and high pressure resistant glass bottle.

[0017] Preferably, the drying in step 3 is carried out at a temperature of 80 to 120° C. for 8 to 12 hours.

[0018] The application of the anthracene-based MOFs crystalline material is to use the anthracene-based MOFs crystalline material for detecting the nitroaromatic explosive trinitrophenol (TNP).

[0019] The method for detecting the nitroaromatic explosive trinitrophenol (TNP) using anthracene-based MOFs crystalline materials is as follows:

[0020] 1. Grind the anthracene-based MOFs crystalline material into a uniform powder with a particle size of 200 to 500 nm, add the powder into ethanol and stir evenly to obtain a stable suspension, which is used as a fluorescent probe solution for detecting trinitrophenol (TNP); the concentration of the anthracene-based MOFs crystalline material in the suspension is 1 mg / mL to 3 mg / mL;

[0021] 2. Using a fluorescence spectrometer, with a laser excitation of 390nm wavelength, detect the fluorescence signal intensity A0 of the test solution at 443nm; add the fluorescent probe solution to the test solution and mix evenly, and detect the fluorescence signal intensity A1 of the mixed solution at 443nm. If A1<A0, it is determined that the test solution contains trinitrophenol (TNP).

[0022] The anthracene-based MOFs crystalline material of the present invention is a MOFs crystalline material with an anthracene functional group and a three-dimensional periodic network structure formed by self-assembly of a tri-ligand and a cadmium metal ion, wherein the cadmium ion, 2,3,5,6-tetrachloroterephthalic acid, 4,4'-stilbene dicarboxylic acid and 9,10-bis(N-benzimidazole)anthracene ligands are self-assembled to form a three-dimensional network structure with orderly distribution of four primitives through a solvent-thermal one-pot synthesis method, and has thermal stability and chemical stability, and has the characteristics of high crystallinity, good reproducibility, high purity, etc. The synthesis method of the present invention is simple and easy to operate, has mild conditions and high repeatability.

[0023] The anthracene-based MOFs crystalline material prepared by the present invention is an electron-rich structure with a large π bond, and can undergo electron transfer and energy transfer with electron-deficient nitroaromatic explosives, thereby causing a significant weakening of the fluorescence signal of the anthracene-based MOFs material, and can detect trace trinitrophenol (TNP) with a concentration of 0 to 5 ppm. At the same time, it is selective for TNP and is not affected by various nitroaromatic explosives such as nitrobenzene (NB) and dinitrobenzene (1,2-DNB, 1,3-DNB, 1,4-DNB), and can be used in the field of environmental pollutant fluorescence sensors. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] Figure 1This is a crystal structure diagram of the anthracene-based MOFs crystalline material prepared in Example 1; A is the asymmetric unit, and B is the topological structure diagram.

[0025] Figure 2 XRD comparison diagram of anthracene-based MOFs crystalline material prepared in Example 1; A is the data curve of theoretical simulation, and B is the data curve of experimental measurement.

[0026] Figure 3 This is the thermogravimetric curve of the anthracene-based MOFs crystalline material prepared in Example 1.

[0027] Figure 4 Solid-state fluorescence excitation and emission spectra of the anthracene-based MOFs crystalline material prepared in Example 1.

[0028] Figure 5 This is the fluorescence spectrum of the anthracene-based MOFs probe solution prepared in Example 1 before and after the addition of TNP.

[0029] Figure 6 This is the standard curve diagram fitted in Example 1.

[0030] Figure 7 This is a graph showing the fluorescence intensity of the anthracene-based MOFs fluorescent probes prepared in Example 1 for trinitrophenol (TNP), nitrobenzene (NB), dinitrobenzene 1,2-DNB, dinitrobenzene 1,3-DNB and dinitrobenzene 1,4-DNB. DETAILED DESCRIPTION

[0031] The beneficial effects of the present invention are verified by the following examples.

[0032] Example 1: The preparation method of the anthracene-based MOFs crystalline material of this example is specifically carried out according to the following steps:

[0033] 1. Add 1 mol of Cd(NO3)2·6H2O, 1 mol of 2,3,5,6-tetrachloroterephthalic acid, 1 mol of 4,4'-stilbene dicarboxylic acid and 1 mol of 9,10-bis(N-benzimidazolyl)anthracene organic ligand into 8 mL of N,N-dimethylformamide solvent in sequence, and vibrate ultrasonically for 20 minutes to completely dissolve the mixture to obtain a mixed solution;

[0034] 2. The mixed solution was transferred to a 20 mL polytetrafluoroethylene reactor, sealed and placed in a forced air drying oven, heated from room temperature to 100 ° C at a heating rate of 3 ° C / min, and maintained for 72 hours for thermal reaction of the solution. After the reaction was completed, the temperature was cooled to room temperature within 12 hours by setting a cooling rate of 0.1 ° C / min to obtain block crystals;

[0035] 3. Wash the obtained block crystals with mother liquor and ethanol respectively, collect the solids after centrifugation, and dry them in an oven at 80°C for 12 hours to obtain an anthracene-based MOFs crystalline material, which is a transparent yellow regular block crystal material with a purity of 98%.

[0036] The anthracene-based MOFs crystalline material prepared in this example has a crystal structure as shown in the figure below: Figure 1 As shown in the figure, A is the asymmetric unit and B is the topological structure diagram. Its structural characteristics are: the two Cd ions can be regarded as a node, connected by 4Cl-BDC ligands in the c-axis direction to form a chain, and then connected by two STDC ligands in the b-axis direction to form a double-layer chain. The 1D chains in the two directions are connected end to end to form a rectangular network structure along the a-axis direction.

[0037] The XRD spectrum of the anthracene-based MOFs crystalline material prepared in this example is as follows: Figure 2 As shown, A is the data curve of theoretical simulation, and B is the measured data curve of anthracene-based MOFs crystalline material prepared in this example. Figure 2 It can be seen that the test results are fitted with the theoretical data, and it is found that the positions of the diffraction peaks can perfectly coincide with each other, and the positions of the main peaks are also completely consistent. This result shows that the skeleton has good stability and phase purity.

[0038] Figure 3 This is the thermogravimetric curve of the anthracene-based MOFs crystalline material prepared in Example 1. Figure 3 It can be seen that there are two weight loss processes between 25℃ and 800℃. First, the first weight loss state occurs before 300℃, which is caused by the removal of guest solvent molecules. The weight loss in this process is 15.27%. In the second step, an obvious and rapid weight loss phenomenon occurs between 320℃ and 430℃, at which time the framework begins to collapse. In summary, the material has good thermal stability.

[0039] The anthracene-based MOFs crystalline material prepared in Example 1 was ground into a uniform powder, and 5 mg of the powder was placed in 5 mL of ethanol solvent to form a stable suspension with a concentration of 1 mg / mL, which was used as a fluorescent probe. The excitation and emission spectra of the fluorescent probe are shown in FIG. Figure 4 As shown, from Figure 4 It can be seen that under the excitation wavelength of 390 nm, the anthracene-based MOFs fluorescent probe emits a strong fluorescence signal at 443 nm.

[0040] Taking trinitrophenol (TNP) as the object and the anthracene-based MOFs crystalline material prepared in Example 1 as the fluorescent probe, the fluorescence spectrum of the anthracene-based MOFs fluorescent probe before and after the action of TNP was determined by fluorescence titration. The specific method is as follows:

[0041] 1. Grind the anthracene-based MOFs crystalline material into a uniform powder with a particle size of 200-500 nm, take 5 mg of the powder and add it to 5 mL of ethanol and stir evenly to obtain a stable suspension with a concentration of 1 mg / mL, which is used as a fluorescent probe solution for detecting trinitrophenol (TNP);

[0042] 2. Prepare trinitrophenol (TNP) solutions with concentrations of 0, 5, 10, 15, 20, 25, 30, 35, 40, 45, and 50 ppm, add the fluorescent probe solution to each TNP solution and mix evenly, and detect the fluorescence spectrum of each mixed solution at 443 nm. Figure 5 As shown, from Figure 5 It can be seen that when different concentrations of TNP solution are added to the anthracene-based MOFs fluorescent probe solution, the fluorescence intensity at 443nm is significantly weakened, indicating that TNP can cause fluorescence quenching of anthracene-based MOFs. Therefore, the fluorescence detection of TNP can be carried out according to the change of the fluorescence signal of anthracene-based MOFs;

[0043] 3. Prepare trinitrophenol (TNP) solutions with concentrations of 0, 1, 2, 3, 4, and 5 ppm, respectively. Use a fluorescence spectrometer to excite with a laser of 390 nm to detect the fluorescence signal intensity I0 of each TNP solution at 443 nm. Add the fluorescent probe solution to the TNP solution and mix evenly. Detect the fluorescence signal intensity I of the mixed solution at 443 nm, calculate the quenching ratio I0 / I value, and then use the concentration of the TNP solution as the horizontal axis and I0 / I as the vertical axis to fit the points to obtain a fitting curve, as shown in the figure. Figure 6 As shown, from Figure 6 It can be seen that the fitting curve is a linearly related straight line, and the fitting curve conforms to the Stern-Volmer equation I0 / I=K sv [M]+1, where [M] represents the concentration of TNP, K sv is the fluorescence quenching constant, K sv =3.90×10 5 (mol / L) -1 ; This indicates that the detection limit is low and low concentration trinitrophenol (TNP) in the range of 0 to 5 ppm can be detected.

[0044] The anthracene-based MOFs crystalline material prepared in Example 1 was used as a fluorescent probe to test the selectivity of the fluorescent probe to trinitrophenol (TNP). The specific method is as follows:

[0045] 1. Grind the anthracene-based MOFs crystalline material into a uniform powder with a particle size of 200-500 nm, take 5 mg of the powder and add it to 5 mL of ethanol and stir evenly to obtain a stable suspension with a concentration of 1 mg / mL, which is used as a fluorescent probe solution for detecting trinitrophenol (TNP);

[0046] 2. Prepare a nitroaromatic explosive solution with a concentration of 50 ppm; wherein the nitroaromatic explosive is trinitrophenol (TNP), nitrobenzene (NB), dinitrobenzene 1,2-DNB, dinitrobenzene 1,3-DNB, and dinitrobenzene 1,4-DNB;

[0047] 3. Using a fluorescence spectrometer, the fluorescence signal intensity curve of the fluorescent probe solution at 443 nm was detected with laser excitation at a wavelength of 390 nm. Then, the fluorescent probe solution was added to each nitroaromatic explosive solution and mixed evenly, and the fluorescence signal intensity curve of each mixed solution at 443 nm was detected. The obtained fluorescence intensity curve is as follows: Figure 7 As shown, from Figure 7 It can be seen that when the concentration is 50 ppm, TNP can significantly weaken the fluorescence signal of anthracene-based MOFs, while other nitroaromatic explosives nitrobenzene (NB) and dinitrobenzene (1,2-DNB, 1,3-DNB, 1,4-DNB) in the environment with the same concentration do not affect the emission of its fluorescence signal, indicating that the anthracene-based MOFs fluorescent probe prepared in this example is selective for the detection of TNP.

[0048] Example 2: The preparation method of the anthracene-based MOFs crystalline material of this example, the specific steps are as follows:

[0049] 1. Add 2 mol of Cd(NO3)2·6H2O, 0.5 mol of 2,3,5,6-tetrachloroterephthalic acid, 1 mol of 4,4'-stilbene dicarboxylic acid and 2 mol of 9,10-bis(N-benzimidazolyl)anthracene organic ligand into 8 mL of N,N-dimethylformamide solvent in sequence, and ultrasonically vibrate for 20 minutes to completely dissolve them;

[0050] 2. Transfer the mixed solution to a 20mL polytetrafluoroethylene reactor or a pressure-resistant glass bottle, and heat it from room temperature to 120°C in a forced air drying oven at a heating rate of 5°C / min for 72 hours. After the reaction is completed, cool it to room temperature within 48 hours by program cooling to obtain block crystals;

[0051] 3. Wash the obtained block crystals with mother liquor and ethanol respectively, collect the solids after centrifugation and dry them at 80°C overnight to obtain anthracene-based MOFs crystalline material; the anthracene-based MOFs crystalline material is a transparent yellow regular block crystal material with a purity of 98%.

[0052] Example 3: The synthesis method of the anthracene-based MOFs crystalline material of this example, the specific steps are as follows:

[0053] 1. 3 mol of Cd(NO3)2·6H2O, 1 mol of 2,3,5,6-tetrachloroterephthalic acid, 2 mol of 4,4'-stilbene dicarboxylic acid and 1 mol of 9,10-bis(N-benzimidazolyl)anthracene organic ligand were sequentially added into 8 mL of N,N-dimethylformamide solvent, and ultrasonically vibrated for 20 minutes to completely dissolve the mixture to obtain a mixed solution;

[0054] 2. The mixed solution was transferred to a 20 mL polytetrafluoroethylene reactor, sealed, and placed in a forced air drying oven and heated from room temperature to 140°C at a heating rate of 7°C / min for 48 hours; after the reaction was completed, it was cooled to room temperature within 48 hours by program cooling to obtain block crystals;

[0055] 3. Wash the obtained block crystals with mother liquor and ethanol respectively, collect the solids after centrifugation and dry them at 80°C overnight to obtain anthracene-based MOFs crystalline material; the anthracene-based MOFs crystalline material is a transparent yellow regular block crystal material with a purity of 98%.

Claims

1. An anthracene-based MOFs crystalline material, characterized in that The stoichiometric formula of the material is {Cd·(4Cl-BDC) 0.5 (STDC) 0.5 ·L} n , wherein 4Cl-BDC is deprotonated 2,3,5,6-tetrachloroterephthalic acid, STDC is deprotonated 4,4'-stilbene dicarboxylic acid, L is 9,10-bis(N-benzimidazolyl)anthracene, and n is a positive integer; the anthracene-based MOFs crystalline material crystallizes in the triclinic P-1 space group, and its structure is topological symbol {3 6 ·4 18 5 3 ·6} 8-connected 3D network; the unit cell parameters are: α=116.983(8) ° , β=95.644(8) ° , γ=102.146(9) ° , the unit cell volume is 2. A method for preparing an anthracene-based MOFs crystalline material according to claim 1, characterized in that The method proceeds as follows:

1. Add soluble cadmium salt, 2,3,5,6-tetrachloroterephthalic acid, 4,4'-stilbene dicarboxylic acid and 9,10-bis(N-benzimidazolyl)anthracene to the solvent in sequence, dissolve all the materials and mix them evenly to obtain a mixed solution; 2. Transfer the mixed solution to a reaction container, seal it and place it in a heating furnace, heat it from room temperature to 80-160°C at a heating rate of 3-10°C / min for a solvothermal reaction for 14-168 hours, and then lower the temperature of the heating furnace to room temperature within 12-24 hours by programmed cooling to obtain block crystals; 3. Wash the block crystals with mother liquor and anhydrous ethanol in turn, collect the solids by centrifugation, and dry them to obtain anthracene-based MOFs crystalline material.

3. The method for preparing anthracene-based MOFs crystalline material according to claim 2, characterized in that The soluble cadmium salt described in step 1 is Cd(NO3)2·6H2O, CdCl2·H2O or (CH3COO)2Cd·2H2O.

4. The method for preparing anthracene-based MOFs crystalline material according to claim 2 or 3, characterized in that The 9,10-bis(N-benzimidazolyl)anthracene described in step 1 has a molecular formula of C 28 H 18 N4.

5. The method for preparing anthracene-based MOFs crystalline material according to claim 2 or 3, characterized in that: The solvent described in step 1 is one or more of N,N-dimethylformamide, N,N-dimethylacetamide, N,N-diethylformamide, methanol, ethanol, acetonitrile and water.

6. The method for preparing anthracene-based MOFs crystalline material according to claim 2 or 3, characterized in that: The molar ratio of the soluble cadmium salt to the organic ligand 2,3,5,6-tetrachloroterephthalic acid described in step 1 is (2-5):1, the molar ratio of the soluble cadmium salt to the organic ligand 4,4'-stilbene dicarboxylic acid is (1-3):1, and the molar ratio of the soluble cadmium salt to the organic ligand 9,10-bis(N-benzimidazolyl)anthracene is (1-3):

1.

7. The method for preparing anthracene-based MOFs crystalline material according to claim 2 or 3, characterized in that: The dissolution in step 1 is carried out by mechanical stirring or ultrasonic oscillation, and the stirring or ultrasonic oscillation time is 10 to 60 minutes.

8. The method for preparing anthracene-based MOFs crystalline material according to claim 2 or 3, characterized in that: The programmed cooling procedure described in step 2 is: cooling at a cooling rate of 0.1°C / min to 0.5°C / min.

9. The use of an anthracene-based MOFs crystalline material according to claim 1, characterized in that The application is to use the anthracene-based MOFs crystalline material to detect the nitroaromatic explosive trinitrophenol.

10. The use of an anthracene-based MOFs crystalline material according to claim 9, characterized in that The method for detecting the nitroaromatic explosive trinitrophenol using anthracene-based MOFs crystalline material is as follows:

1. Grind the anthracene-based MOFs crystalline material into a uniform powder with a particle size of 200 to 500 nm, add the powder into ethanol and stir evenly to obtain a stable suspension, which is used as a fluorescent probe solution for detecting trinitrophenol; the concentration of the anthracene-based MOFs crystalline material in the suspension is 1 mg / mL to 3 mg / mL; 2. Using a fluorescence spectrometer, with a laser excitation of 390nm wavelength, detect the fluorescence signal intensity A0 of the test solution at 443nm; add the fluorescent probe solution to the test solution and mix evenly, and detect the fluorescence signal intensity A1 of the mixed solution at 443nm. If A1<A0, it is judged that the test solution contains trinitrophenol.

Citation Information

Patent Citations

  • BE562948A

  • 9,10-diphenylanthracene organic single crystal scintillator, preparation method therefor, and use thereof

    WO2021139097A1